(3fNHI GdacQ aj eUWdM Cgd GdCKQs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdJUGfja ai EUWdGM Cgd GdMOjK aO cKQJ ddCFeI ai GdbOje hGdMOjK aSCdfi HYV GdENhGf Cf CdNU dg Gdege ef Pdc SejJgG fNHI GdacQ ai eUWdM Cgd GdCKQ Ydi JQJjH EHJcQJg s
(3BNQgG (B:s
(3adjQGLY dgG eHShWGJgG djMUd Gdhba Ydi MbGFbgG hGddg Gdehab hGdgGOi dG Edg EdG ghYdjg JhcdJ hEdjg CfjH hMSHfG Gddg hfYe Gdhcjd hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQg MOjK Yf GdfHi Udi Gddg Ydjg hSdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs